2021
DOI: 10.3390/rs13061078
|View full text |Cite
|
Sign up to set email alerts
|

Retracking Cryosat-2 Data in SARIn and LRM Modes for Plateau Lakes: A Case Study for Tibetan and Dianchi Lakes

Abstract: This paper estimates lake level variations over two small and adjacent lakes in the Tibetan plateau (TP), namely Gemang Co and Zhangnai Co, as well as the inland Dianchi Lake in China using CryoSat-2 SARIn-mode and LRM 20-Hz waveforms over the period of 2011–2018. Different retrackers and a dedicated data editing procedure have been used to process CryoSat-2 data for determining the lake level time series. The lake level estimations are indirectly validated against those from Jason-2 in TP and from in situ dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The altitude is about 1609 m. The length from east to west is about 178 km, and the width from north to south is about 60 km. Lake Issyk-Kul has an area of 6236 km 2 , a storage capacity of 1378 km 3 , and a depth of about 300–700 m. It is a year-round unfrozen lake with annual precipitation of about 200–300 mm [ 28 ]. Lake Issyk-Kul is the largest alpine saltwater lake in Central Asia.…”
Section: Methodsmentioning
confidence: 99%
“…The altitude is about 1609 m. The length from east to west is about 178 km, and the width from north to south is about 60 km. Lake Issyk-Kul has an area of 6236 km 2 , a storage capacity of 1378 km 3 , and a depth of about 300–700 m. It is a year-round unfrozen lake with annual precipitation of about 200–300 mm [ 28 ]. Lake Issyk-Kul is the largest alpine saltwater lake in Central Asia.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the quality of inland water level measurements is tested using only SAR mode [68,69], while in [70] some study regions were observed in SAR mode, and some other lakes were covered in LRM. In addition, in [71,72] LRM is utilized to evaluate the performance of different missions for measuring inland water levels, whereas both LRM and InSAR modes are used to test different retracking algorithms [73] showing that CryoSat-2 InSAR mode data can be used to monitor small inland water bodies that have not been measured by other altimetry missions. Based on these publications, the CryoSat-2 mission can deliver useful water level observations over inland water bodies worldwide, as even the conventional LRM mode of the altimeter delivers good results.…”
Section: Radar Altimetry Satellite Missionsmentioning
confidence: 99%
“…Moreover, having common study areas, seven lakes in the Tibetan Plateau, AMPDR using CryoSat-2 InSAR data outperform the ImpMWaPP retracker. Furthermore, in the same year, a new retracker called APD-PPT was presented using also CryoSat-2 data to monitor inland water level variations [73]. This new algorithm combines the adaptive peak detection (APD) with the PPT retracker since the sub-waveform is formed based on the APD-detected primary peak, and retracked by the PPT algorithm.…”
Section: Novel and Improved Retracking Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of using altimeter data such as Jason-2 to detect and GRACE results is consistent, such as in the study of lake water levels on the Tibetan Plateau [100]. For the problem of land pollution in inland waters, if we want to improve the observation accuracy of altimetry data in inland waters, we can use the waveform retracking algorithm of inland lakes based on waveform purification technology [101][102][103][104][105].…”
Section: Availability Of Datamentioning
confidence: 99%